Perinuclear Antineutrophil Cytoplasmic Autoantibodies and Anti-Saccharomyces Cerevisiae Antibodies as Serological Markers Are Not Specific in the Identification of Crohn’s Disease and Ulcerative Colitis - Vishal Anand; Anthony S Russell; Ross Tsuyuki; Richard Fedorak (Canadian Journal of Gastroenterology)
OBJECTIVE: To evaluate the diagnostic accuracy of perinuclear antineutrophil cytoplasmic autoantibodies (pANCAs) and anti-Saccharomyces cerevisiae antibodies (ASCAs), as single agents and in combination, for the diagnosis of Crohn’s disease (CD) and ulcerative colitis (UC), including in cases of indeterminate colitis (IC).